Recursos didácticos y su incidencia en los logros de aprendizaje en el área de ciencias naturales de los estudiantes de educación básica media de la Escuela “Lizardo García avilés” del recinto Lechugalito. Año lectivo 2014 – 2015. Plan de capacitación docente - Mariño Villarruel, Carlos Armando (2016)
The use of teaching resources in the teaching-learning process in the natural sciences must integrate properly and is very attractive for students to develop their abilities and skills and reach a comprehensive education as human beings. The teaching resources should always be considered as a support to the educational process. The teaching resource is a key factor for the student to develop their own knowledge, with the use of various educational resources made with materials of the environment in the various areas of learning a more productive learning will be achieved and managed to increase the motivation to learn any subject. In the School of Basic Education "Lizardo García Avilés" located in the rural area it has hardly reached the help of the education authorities, so evident in classrooms lack of teaching resources that are pampering reflected in the moment the teacher gives classes mechanically; It has also been observed weak involvement of teachers to develop these resources thereof having a very low cost, but lack teachers have to develop them, arguing cost. Students are shown uninterested in time to hear his lectures; since they are limited to pencil, notebook and slate work; They do not manipulate resources to help confirm, develop, consolidate and verify the contents are reviewed with students and to encourage and familiarize on this. There is a willingness of teachers to participate in training events on the development of educational resources for the teaching of natural sciences. It was of great importance to develop this research because it helped strengthen the teaching action on the use of educational resource for learning achievement in the natural sciences. This research was aimed to establish the incidence of the teaching resource in learning achievement in the area of Natural Sciences School students Lizardo García Avilés "in the school year 2014 - a methodological design 2015.Comprenderá Flexible use of descriptive conclusive research, conclusive causal research and exploratory research, the main. This research was important because teachers and students are committed to the institution concerning educational innovations in aspects of teaching and learning aimed at training people in harmonious coexistence with the community aimed at the defense of its natural sciences environment. a critical hub for research were identified: How the application of teaching resources affects the achievement of the learning area Natural Sciences students of the School of Basic Education "Lizardo García Avilés" enclosure Lechugalito, parish Zapotal, Ventanas Canton, Province of the Rivers? In this research the following general objective was posed: To evaluate the application of teaching resources and its impact on learning achievements in the area of Natural Sciences students of the School of Basic Education "Campus Lizardo García Avilés Lechugalito of Zapotal Parish , Canton Ventanas, Los Rios Province in the 2014-2015 school year. It has raised the following hypothesis for your demonstration: The limited application of teaching resources negatively affects the learning achievement in the area of Natural Sciences students of the School of Basic Education "Lizardo García Avilés Lechugalito of Campus Zapotal Parish, Canton Ventanas, Los Rios Province in the 2014-2015 school year, Teacher Training Plan development and implementation of teaching resources for learning achievement in the area of Natural Sciences students in elementary and secondary education at the School of Basic Education Lizardo García Avilés: Finally the design of a proposal arises Lechugalito enclosure, the Zapotal parish Ventanas Canton. The aim of the proposal lies in the implementation of training workshops to teaching sector for the development of educational resources to achieve the learning of natural sciences.